Fund Supported Adjustment Programs and Economic Growth - Knight, Malcolm (Occasional Papers; Occasional Paper ;, 1985)
This is the first of a group of papers dealing with various aspects of Fund-supported adjustment programs. The other two, The Global Effects of Fund-supported Adjustment Programs by Morris Goldstein and Fund-Supported Programs, Fiscal Policy, and Income Distribution by the Fiscal Affairs Department, will also be published in the Fund's Occasional Paper Series.